Post-Durban Agriculture and Climate Change Workshop for Eastern Africa, Arusha, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
On February 14-16 2012, CCAFS in cooperation with the Common Market for Eastern and Southern Africa (COMESA) and the East African Community (EAC) organized a workshop in Arusha, Tanzania, aiming to review the outcomes of the COP 17 meetings in Durban in 2011. Eastern African government officials, farmers' and civil society organisations and university representatives participated in the workshop.